THE EFFECT OF FINANCIAL PERFORMANCE AND AUDIT COMMITTEE SIZE ON FINANCIAL DISTRESS IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Novi Akhsani; Eka Salfa Wulandari (Asosiasi Dosen Muda Indonesia, 2026)
This study aims to examine the effect of financial performance and audit committee size on financial distress in manufacturing firms listed on the Indonesia Stock Exchange. Financial performance is represented by profitability and liquidity, while financial distress is measured using a modified Altman model. The research applies a quantitative approach using secondary data derived from published financial statements. The sample consists of selected manufacturing companies that meet specific criteria and are observed over a continuous period. Data analysis is conducted using panel data regression to evaluate both partial and simultaneous effects of the independent variables on financial distress. The findings indicate that profitability and liquidity significantly influence financial distress, suggesting that firms with stronger financial performance are less likely to experience financial difficulties. In contrast, audit committee size does not show a significant individual effect, although it contributes jointly with financial performance variables. These results highlight the importance of financial indicators in predicting corporate financial stability.